What do I need from myself as a student but also from others to reduce the impact of stress on academic performance? Self-efficacy and social support - Pǎduraru, Ancuţa Elena; Soponaru, Camelia; Dîrţu, Cǎtǎlin; Gavrilovici, Ovidiu; Bucuţǎ, Mihaela Dana (Frontiers in Education, 2025)
IntroductionThe literature emphasizes the link between academic stress and academic performance and the fact that the most vulnerable students are first-year students, but we still need to understand the underlying mechanism for forming targeted intervention strategies and the protective factors. The main objective of the present study was to test the mediating effect of self-efficacy and social support on the relationship between academic stress and academic performance. We also aimed to identify the main sources of stress and their significant sources of support.MethodsData were collected via an online survey platform in January 2024, with 436 students, with a mean age of 19.99 ± 3.72, responding affirmatively to our invitation. Thus, in this cross-sectional study, the sample was a convenience sample.ResultsThe highest source of stress was the pressure to perform, followed by time restraints, perceptions of workload and examinations, and self-perceptions. The highest level of support is obtained from significant others, followed by family support and, last, friends' support. Both self-efficacy and social support partially mediate the effect of academic stress on academic performance.ConclusionsOur results suggest that one way to improve students' performance, even when they experience academic stress, is to increase their levels of social support, especially from family, as well as their self-efficacy. These results can be used by services that provide psychological support to students in order to design and implement intervention programs.